2021
DOI: 10.1101/2021.10.07.462409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and retinal remodeling in the brown anole lizard (Anolis sagrei)

Abstract: Background. The fovea, a pit in the retina, is believed to be important for high-acuity vision and is a feature found in the eyes of humans and a limited number of vertebrate species that include certain primates, birds, lizards, and fish. At present, model systems currently used for ocular research lack a foveated retina and studies investigating fovea development have largely been limited to histological and molecular studies in primates. As a result, progress towards understanding the mechanisms involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 51 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…A drop in cellularity from hatchling to adulthood raises the question of whether cell death is occurring within the retina. Studies in embryonic rodents, chicks, turtles and anoles have shown that a significant portion of cell death occurs in retina cell layers during development, but that cell death slows and largely ceases shortly after birth or hatching (Beazley et al, 1987; Cook et al, 1998; Francisco-Morcillo et al, 2004; Rasys, Pau, Irwin, Luo, Kim, Wahle, Trainor, et al, 2021; Rasys, Pau, Irwin, Luo, Kim, Wahle, Menke, et al, 2021). Although we did not specifically look for markers of cell death in retinal sections, we did not observe any evidence of pyknotic cells within our sections across the age groups, suggesting that if cell death is occurring, it is likely minimal.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A drop in cellularity from hatchling to adulthood raises the question of whether cell death is occurring within the retina. Studies in embryonic rodents, chicks, turtles and anoles have shown that a significant portion of cell death occurs in retina cell layers during development, but that cell death slows and largely ceases shortly after birth or hatching (Beazley et al, 1987; Cook et al, 1998; Francisco-Morcillo et al, 2004; Rasys, Pau, Irwin, Luo, Kim, Wahle, Trainor, et al, 2021; Rasys, Pau, Irwin, Luo, Kim, Wahle, Menke, et al, 2021). Although we did not specifically look for markers of cell death in retinal sections, we did not observe any evidence of pyknotic cells within our sections across the age groups, suggesting that if cell death is occurring, it is likely minimal.…”
Section: Resultsmentioning
confidence: 99%
“…Foveal areas undergo periods of localized elongation followed by retraction. During ocular retraction, pit formation and the majority of photoreceptor packing occurs (Rasys, Pau, Irwin, Luo, Kim, Wahle, Trainor, et al, 2021; Rasys, Pau, Irwin, Luo, Kim, Wahle, Menke, et al, 2021). It is possible that ocular retraction, particularly along the z-axis, may persist for a brief period after hatching and during ocular expansion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations